2020
DOI: 10.5603/cj.a2018.0026
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between pulse waveform analysis indices, endothelial function and clinical outcomes in patients with peripheral artery disease treated using percutaneous transluminal angioplasty during a one-year follow-up period

Abstract: Background: Several predictors of clinical outcomes after percutaneous transluminal angioplasty

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Therefore, it may be hypothesized that the measurement of FMD in adult FH patients is robust and does not provide any useful insight into CVD risk stratification. On the other hand, other studies suggest that FMD does not correlate with clinical outcomes in patients without FH; thus, further comprehensive studies are required to better estimate the clinical importance of FMD [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it may be hypothesized that the measurement of FMD in adult FH patients is robust and does not provide any useful insight into CVD risk stratification. On the other hand, other studies suggest that FMD does not correlate with clinical outcomes in patients without FH; thus, further comprehensive studies are required to better estimate the clinical importance of FMD [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gupta et al reported a positive correlation between FMD and ABI in young males post myocardial infarction in India [25]. However, Vigna et al found no significant correlation between ABI and FMD in a dyslipidemic population [26], and Kaczmarczyk et al reported no correlation between ABI, toe-brachial index and FMD among patients with PAD [27]. Taken together with our finding of no correlation between FMD and ABI among HD patients, it appears that the relationship between FMD and ABI varies among different populations.…”
Section: Discussionmentioning
confidence: 99%
“…Toe-brachial index (TBI) increased after endovascular treatment and remained at one level. Despite the lack of spectacular results in terms of indicators of vascular function, researchers point to the benefits of the PTA procedure due to the clinical improvement in patients, as assessed by pain-free walking distance and maximal walking distance [ 89 ].…”
Section: Fmd In Patients With Cardiovascular Diseasementioning
confidence: 99%